Tribological analysis of the plain bearings in an external gear pump. Issue 1 (February 2021) - Brinkmann, Lars; Kock, Stefan; Lang, Jochen; Knoll, Gunter
Abstract: Tribological loads in the plain bearings of external gear pumps are influenced by system-specific parameters (e.g. elasticity of the components, micro-geometry and manufacturing tolerances) and the operating point (rotation speed, operating pressure and temperature of the pressure medium). Due to the pressure build-up in the tooth chambers, fluctuating radial forces are acting on the gear shafts and lead to complex deformations of the bearing bushings and the housing. These deformations have an influence on the tribological loads in the plain bearings. To decrease tribological loads and failure rates, it is possible to modify the plain bearings in terms of their micro-geometry (e.g. clearance and contours) or to take constructive measures on the overall system (e.g. on the bearing bushings). Therefore, it is necessary to understand the influences of external loads, elastic environment and micro-geometry on the tribological loads in the plain bearings. This paper describes the first steps to understand these interactions by building up a simulation model of a specific external gear pump using the MBS/EHD-tool FIRST developed by IST [1]. The focus is to evaluate the required modeling depth regarding the consideration of an elastic housing.